Pengaruh Konsentrasi Tepung Ikan Cakalang (Katsuwonus pelamis) dan Lama Pengeringan Terhadap Karakteristik Organoleptik Tortilla Chips Ubi Jalar Ungu (Ipomoea batatas L.) - Breemer, Rachel; Lahagu, Ovdarlin; Palijama, Syane (Universitas Pattimura, 2023)
Tortilla chips are a type of snack that contains high levels of carbohydrates compared to their protein content. So, tortilla chips need to be made with more local products from the area, like purple sweet potatoes and skipjack fish flour. his study aims to determine the appropriate concentration of skipjack tuna (Katsuwonus pelamis) addition and drying time on the organoleptic characteristics of purple sweet potato tortilla chips (Ipomoea batatas L.) This research was tested statistically non-parametrically using the Friedman Test The results of the study, it can be concluded that the treatment of skipjack tuna flour concentration of 10% and drying time of 6 hours is the treatment with the best organoleptic characteristics by hedonic test and hedonic quality test of tortilla chips successively with characteristics including: color 3.20 (like) and 3.0 (purple), taste 3.16 (like) and 2.79 (slightly taste skipjack tuna), crispness 3.08 (like) and 3.37 (crispy), flavor 3.12 (like) and 3, 29 (scented with skipjack tuna) and overall 3.45 (like it).